Color tunable aerogels/sponge-like structures developed from fine fiber membranes. Issue 6 (21st February 2022) - Villarreal, Alexa; Barbosa, Raul; Bose, Saptasree; Srivastava, Bhupendra B.; Padilla-Gainza, Victoria; Lozano, Karen
Abstract : The development of macroscopic aerogels from 1D systems, such as nanofibers, has resulted in a novel pathway to obtain porous and lightweight architectures. Abstract : The development of macroscopic aerogels from 1D systems, such as nanofibers, has resulted in a novel pathway to obtain porous and lightweight architectures. In this work, bright green, red, and tunable color emitting aerogels were obtained with luminescent nanofibers as the precursor system. A simple, low cost, and environmentally friendly process is followed where luminescent fillers are encapsulated within fibers which were subsequently freeze-dried to form 3D aerogels and sponge-like structures. Moreover, the aerogels/sponge-like structures show higher photoluminescence intensity than the fiber mats due to an increase of porosity which provides higher and direct interaction with the fillers and therefore an efficient light absorption resulting in higher luminescence. Manganese doped zinc germanate (Mn: Zn2 GeO4 ) nanorods and chromium doped zinc gallate (Cr: ZnGa2 O4 ) nanoparticles were used as the source of green and red emissions respectively. By precisely adjusting the stoichiometric ratios of nanorods and nanoparticles within the nanofibers, a broad spectrum output is obtained from the final aerogels. We foresee that these types of photoluminescent aerogels have promising potential applications in a variety of fields such as display devices, solid-state lighting, sensors, etc.